Effect of Liuzijue Combined with Inspiratory Muscle Training on Patients with Chronic Obstructive Pulmonary Disease - WANG Qing; LIU Siyuan; CAO Haihao; QU Xinjie; ZHANG Linlin; BI Hongyan (康复学报)
ObjectiveTo explore the effect of Liuzijue combined with inspiratory muscle training on lung function, exercise endurance and quality of life of patients with chronic obstructive pulmonary disease (COPD).MethodsA total of 60 patients with COPD in the rehabilitation department of the Affiliated Hospital of Shandong University of Traditional Chinese Medicine from March 2020 to June 2021 were randomly divided into control group, inspiratory muscle training group and Liuzijue combined with inspiratory muscle training group (combined group), with 20 cases in each group. The control group received routine drug treatment and rehabilitation training, including rehabilitation training 30 minutes a time, once a day, five days a week, lasting for eight weeks. The inspiratory muscle training group received the inspiratory muscle training on the basis of the control group, 20 minutes a time, once a day, five days a week, lasting for eight weeks. On the basis of the inspiratory muscle training group, the combined group received "six character formula" training of fitness Qigong, 30 min a time, once a day, five days a week, lasting for eight weeks. Before treatment and after eight weeks of treatment , the percentage of forced breathing in the first second (FEV1%pred) and the maximum inspiratory pressure (MIP) were used to evaluate the patient's lung function; 6 minutes walking test (6MWT) was used to evaluate the patient's exercise tolerance; COPD assessment test (CAT) was used to evaluate the quality of life of patients.ResultsCompared with those before treatment, the FEV1%pred, MIP and 6MWT of all three groups increased significantly after treatment, CAT score decreased significantly after treatment, and the differences were statistically significant (P<0.05). Compared with the control group, the FEV1%pred, MIP and 6MWT of the inspiratory muscle training group and the combined group were significantly higher after treatment, and the CAT score was significantly lower, and the differences were statistically significant (P<0.05). Compared with the inspiratory muscle training group, the FEV1%pred, MIP, and 6MWT of the combined group were significantly higher after treatment (P<0.05), and the CAT score was significantly lower, and the difference was statistically significant (P<0.05).ConclusionLiuzijue combined with inspiratory muscle training can effectively improve the lung function, exercise endurance and quality of life of patients with COPD, which is recommended for clinical application.